Injeção de dejetos líquidos de suínos no solo e inibidor de nitrificação como estratégias para reduzir as emissões de amônia e óxido nitroso - Damasceno, Fabiano (2010)
Injection of pig slurry (PS) into the soil and the addition of nitrification inhibitors have been used in some countries as a strategy for manure nitrogen (N) preservation and mitigation of its pollution potential. The effect of these practices has been assessed mainly on N losses by ammonia (NH3) volatilization and the emission of greenhouse gases (GHGs). Research in this area is still incipient in Brazil. This study was carried out to evaluate the effect of the injection of pig slurry into the soil and the use of the nitrification inhibitor dicyandiamide (DCD) in the commercial product Agrotain plus (DCD 81%) on N losses by NH3 volatilization and the emission of nitrous oxide (N2O). Two field experiments were carried out over a Paleudalf under no tillage and oat straw mulching from May 2008 to May 2010. On the experiment 1, three treatments were compared over 61 days: PS (60 m3 ha-1) on soil surface, PS injected into the soil, and a control without PS. The accumulated N-NH3 loss, over 196 hours, with PS on soil surface was 4,8 kg N-NH3 ha-1, which was decreased to only 0,03 kg N-NH3 ha-1 with PS injected into the soil. On the experiment 2, five treatments were compared: two with PS (60 m3 ha-1) on soil surface or injected into the soil, two with the addition of Agrotain plus (7 kg ha-1) to the PS prior its application on soil surface or injection into the soil, and also a control without PS or Agrotain plus. The accumulated N-NH3 volatilization over 501 hours was reduced from 8,1 kg N-NH3 ha-1 on the PS on soil surface treatment to only 0,12 kg N-NH3 ha-1 when PS was injected into the soil. The addition of Agrotain plus in surface-applied PS increased the accumulated NH3 volatilization on 6,2 kg N-NH3 ha-1 (77%). On the other hand, the nitrification inhibitor decreased the N-N2O emissions by 74% at the average of both PS application methods. Our results showed that the injection of pig slurry into the soil with the DCD addition as a nitrification inhibitor preserved the ammonia nitrogen in the slurry and reduced the N2O emissions contributing to the mitigation of the pig farming pollution potential.